METHODS OF USING IMMERSION TEACHING MODERN GREEK LANGUAGE IN A HIGHER EDUCATION - Voyevutko, Natalya; Kuligina, Olena (Advanced Education, 2016)
Immersion as a special bilingual teaching method is intended to plunge students into the learning environment by the way of transforming the teaching process into a language environment. Learning the Modern Greek language at the Mariupol State University in the process of training the Modern Greek-Ukrainian translators based on immersion methods emerges the actual methodological problem which can be solved by revitalizing the method of teaching some special subjects. The method of immersion teaching the Modern Greek language at the Higher Educational Establishment has been highlighted in the paper based on the special course of subjects under the title “Annotating and Abstracting Texts (Modern Greek language)” of the optional course for students obtaining the Master’s degree. The special course mentioned above has been worked out on the basis of integrity and immersion. Teaching annotating and abstracting in the Modern Greek language accompanied with the methodology support as well as the syllabus and the reference book of clichés ensures the appliances named “Annotating and Abstracting Texts (Modern Greek language)”. The considered work is provided with practical tasks presented in the form of texts of annotations and abstracts, scientific articles, dedicated to the issues of highlighting the actual issues of philology, linguistics, linguodidactics, comparative pedagogics and translation. As the subject is focused on teaching philologists and translators, immersion has some peculiarities. Firstly, it is multilingual as the teaching material is provided in three languages (Modern Greek, Ukrainian and English). Secondly, it is translation-oriented as immersion is realized not only in one main language (here it is the Modern Greek) but into the processes of Modern Greek – Ukrainian and English-Ukrainian translation. The method of using the immersive teaching in the special course is realized in the systematic use of the following principles: 1) harmonization of the learning language and the themes and contents of the language material; 2) gradual increasing of the complexity level of the tasks during the teaching process; 3) gradual increasing in number of the teaching materials in the Modern Greek language. The partial immersion in the course is being gradually changed by the full immersion.